Maternal Prenatal Stress, Thyroid Function and Neurodevelopment of the Offspring: A Mini Review of the Literature - Anifantaki, Foteini; Pervanidou, Panagiota; Lambrinoudaki, Irene; Panoulis, Konstantinos; Vlahos, Nikos; Eleftheriades, Makarios (Frontiers in Neuroscience, 2021)
Fetal brain is extremely plastic and vulnerable to environmental influences that may have long-term impact on health and development of the offspring. Both the Hypothalamic-Pituitary-Adrenal (HPA) and the Hypothalamic-Pituitary-Thyroid (HPT) axes are involved in stress responses, whereas, their final effectors, the Glucocorticoids (GCs) and the Thyroid Hormones (ΤΗs), mediate several fundamental processes involved in neurodevelopment. The effects of these hormones on brain development are found to be time and dose-dependent. Regarding THs, the developing fetus depends on maternal supply of hormones, especially in the first half of pregnancy. It is acknowledged that inadequate or excess concentrations of both GCs and THs can separately cause abnormalities in the neuronal and glial structures and functions, with subsequent detrimental effects on postnatal neurocognitive function. Studies are focused on the direct impact of maternal stress and GC excess on growth and neurodevelopment of the offspring. Of particular interest, as results from recent literature data, is building understanding on how chronic stress and alterations of the HPA axis interacts and influences HPT axis and TH production. Animal studies have shown that increased GC concentrations related to maternal stress, most likely reduce maternal and thus fetal circulating THs, either directly or through modifications in the expression of placental enzymes responsible for regulating hormone levels in fetal microenvironment. The purpose of this review is to provide an update on data regarding maternal stress and its impact on fetal neurodevelopment, giving particular emphasis in the interaction of two axes and the subsequent thyroid dysfunction resulting from such circumstances.